(untitled) (Journal of Hama University, 2022)
The study aimed to identify the effectiveness of the use of Motor stories in distinguishing the false belief task of the kindergarten child, and the experimental method was used. From the method of Motor Stories and the scale of False Belief Task, the study yielded the Following Results: There are statistically significant differences between the mean scores of the children of the experimental group and the control group in the direct dimensional application, as the value of (T) reached (2.309) with a level of significance (0.000. There are statistically significant differences between the average scores of the children of the experimental group in the direct pre and post applications; As the value of (T) reached (3.207) with a level of significance (0.000). There is no statistically significant difference between the average scores of the children of the control group in the direct pre and post applications. The value of (T) reached (0.366) at a level of significance (0.467). There are statistically significant differences between the average scores of the children of the experimental group in the two applications, the direct post and the delayed one. As the value of (T) reached (2.481) with a significance level of (0.000).